2010
DOI: 10.1007/978-3-642-13470-8_18
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and Personalization of Criteria in Recommender Systems

Abstract: Abstract. A user's informational need and preferences can be modeled by criteria, which in turn can be used to prioritize candidate results and produce a ranked list. We examine the use of such a criteria-based user model separately in two representative recommendation tasks: news article recommendations and product recommendations. We ask the following: are there nonlinear interactions among the criteria; and should the models be personalized? We assume that that user ratings on each criterion are available, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Since independence of criteria usually was not given with real live decision problems [48], and since criteria interaction might be experienced differently among users [49], the possibility to model interaction between criteria was an important feature of "AniFair". An example on how the aggregation of interacting criteria could not be modeled by a weighted mean could be found in Čaklović [50].…”
Section: Discussionmentioning
confidence: 99%
“…Since independence of criteria usually was not given with real live decision problems [48], and since criteria interaction might be experienced differently among users [49], the possibility to model interaction between criteria was an important feature of "AniFair". An example on how the aggregation of interacting criteria could not be modeled by a weighted mean could be found in Čaklović [50].…”
Section: Discussionmentioning
confidence: 99%
“…Besides accuracy, specificity has also gained deserved attention among researchers (He et al, 2016;Ramalho et al, 2014). Furthermore, timeliness has got a very important place on the list of evaluation metrics for recommendation systems in health care and other healthrelated systems (Caamares and Castells, 2018;Fong et al, 2011;O'Mahony and Smyth, 2010;Wolfe and Zhang, 2010;Xu et al, 2018;Zhang et al, 2018). Adaptability as an evaluation metric for recommendation systems in health care has also featured prominently in literature (Nathanson et al, 2007;Wiesner and Pfeifer, 2014;Wu et al, 2012;Yang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the most important quality that is looked for in a recommendation system is its ability to provide personalized recommendations to its users. Its ability to infer the user's needs and satisfy it (Wolfe and Zhang, 2010). This is seen in the recommendation systems available in health care.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, this problem is usually avoided by considering independent criteria (Cong et al., ; Göker & Myrhaug, ). Nevertheless, other works (Carterette, Kumar, Rao, & Zhu, ; Eickhoff et al., ; Saracevic, ; Wolfe & Zhang, ) have shown that relevance criteria usually interact. For instance, Carterette et al.…”
Section: Multidimensional Relevance Aggregation In Irmentioning
confidence: 97%